Platelet Rich STROMA, the Combination of PRP and tSVF and Its Potential Effect on Osteoarthritis of the Knee - Stevens, Hieronymus P.; van Boxtel, Joeri; van Dijck, Robbert; van Dongen, Joris A. (Applied sciences, 2020)
(1) Background: osteoarthritis (OA) of the knee is a degenerative disease accompanied by pain, reduced mobility and subsequent decrease in quality of life. Many studies on OA of the knee have reported that using an intercellular acting-derivate like platelet-rich plasma (PRP) results in a limited effect or none at all. Authors hypothesized that adding tissue-Stromal Vascular Fraction (tSVF) to PRP (Platelet Rich Stroma (PRS)) would reduce pain and improve functionality in osteoarthritis of the knee. (2) Methods: a consecutive case series of fifteen patients (aged 43–75 years) suffering from OA of the knee (Kellgren–Lawrence stage two to three) were treated with a single injection of autologous PRS. tSVF was mechanically isolated by means of the fractionation of adipose tissue (FAT) procedure. Clinical evaluation was done using a visual analogue score (VAS) score, an adapted Western Ontario and McMaster Universities Osteoarthritis index (WOMAC) and Lysholm score at fixed time points: pre-injection as well as three, six and twelve months post injection. (3) Results: VAS and WOMAC scores improved significantly after twelve months (p < 0.01 and p < 0.05). Lysholm instability scores were also improved at twelve months (p > 0.05) in comparison to pre-injection measurements. No complications were seen in any of the patients. One patient was excluded due to a total knee arthroplasty. (4) Conclusions: a single injection with PRS for OA of the knee seems to lead to an improvement of function and simultaneous reduction of pain and joint stiffness for a period of twelve months. Further controlled trials are required to determine the optimal treatment regimen and evaluate long-term results.